”You Must Swear [...] That Care for the Well-Being and Health of Women in Labor and Their Infants Shall Be the Only Objective of Your Work.” Midwives in the Galician Autonomy — Statistical and Geographical Analysis by Counties - Rejman, Sabina (Studia Historiae Oeconomicae, 2019)
The study analyses the number of midwives in the counties of Eastern and Western Galicia in census years 1869, 1880, 1890, 1900 and 1910, and the ratios per cadastral commune, 10,000 square kilometers, 10,000 civilians and 10,000 women in a county. The analysis was based on Austrian and Galician statistical reports. The results of the study confirmed that Eastern Galicia outnumbered Western Galicia in terms of midwives. However, it was in Western Galicia where the rate of growth was higher, and the effects of the 1910 collapse more moderate. This could have been due to an amendment to the 1897 midwifery regulations. The position of individual counties changed, depending on the year and the specific measure. In Eastern Galicia, Lisko county ranked the worst and Horodenka, Śniatyń, Tarnopol, Trembowla, and Brzozów counties ranked the best. In Western Galicia, Limanowa county ranked the worst, while Brzesko, Kraków, Łańcut, Wadowice, Przeworsk, and Podgórze counties ranked the best. There is a strong positive correlation between the rank and natural conditions (water, soil, climate), type of crops, agricultural development and processing, transport system (road and rail), population, and stimulating function of large urban centers. Favorable conditions were correlated with higher values in measures of the number of midwives.